Ethnomedicinal Plants Used in the Treatment of Various Ailments by Bhil Tribe of Ratlam District (Madhya Pradesh) India - Jadhav, Dinesh (Indian Forester, 2011)
Frequent ethnomedicinal surveys were conducted between August, 2004 to March, 2007 in different villages of Ratlam district. Results of these surveys indicated that 68 plant species are interestingly used for the treatment of various diseases by the Bhil tribals of the district. Botanical names followed byfamily, local names and the ethnomedicinal uses have been provided.